Efektivitas Pengaruh Penyimpanan Sementara dan Pengelolaan Limbah B3 Berdasarkan Hukum Lingkungan Di Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Hazardous and toxic waste (B3) is waste resulting from a production process, whether industrial or other business activities, where people who live there usually find or produce rubbish, waste water or other activities that are not managed properly, which will have an impact on creatures and the environment. around it, because its nature and concentration, whether directly or indirectly, can damage the environment and the health of living creatures around it. B3 waste is waste or waste whose nature and concentration contain toxic and dangerous substances so that it can directly or indirectly damage the environment, harm health and threaten the survival of humans and other organisms. B3 waste is not only produced from industrial activities but household activities can produce several types of waste. The method used is normative legal research by examining the governing laws and regulations. This research aims to determine the relationship between positive legal regulations and the problem of B3 waste and how to deal with B3 waste so that the environment is maintained.